Germanium Doping to Improve Carrier Mobility in CdO Films. (3rd April 2013) - Dakhel, A. A.
Abstract : This investigation addresses the structural, optical, and electrical properties of germanium incorporated cadmium oxide (CdO : Ge) thin films. The focus was on the improvement in carrier mobilityμ to achieve high transparency for near-infrared light and low resistivity at the same time. The properties were studied using X-ray diffraction, SEM, spectral photometry, and Hall measurements. All CdO : Ge films were polycrystalline with high texture orientation along [111] direction. It was observed that it is possible to control the carrier concentration (N e l ) and mobility (μ ) with Ge-incorporation level. The mobility could be improved to a highest value of 91 cm 2 /V·s with Ge doping of 0.25 wt% while maintaining the electrical resistivityρ as low as2.76 × 10 - 4 Ω·cm and good transparency 80 % in the NIR spectral region. The results of the present work proved to select Ge as dopant to achieve high carrier mobility with low resistivity for application in transparent conducting oxide (TCO) field. Generally, the properties found make CdO : Ge films particularly interesting for the application in optoelectronic devices like thin-film solar cells.